Optimal diagonal precoder for multi-antenna communication system - Yan, Z.; Wong, K.M.; Luo, Z.Q. (2003 IEEE 4th Workshop on Signal Processing Advances in Wireless Communications, 2003)
We develop an efficient diagonal matrix precoder which minimizes the lower bound of the average bit error rate (BER) for a multi-antenna wireless communication system with a QR receiver in flat fading channel. The precoder also minimizes the average block error rate at the same time. It provides substantially lower error rates than the MMSE precoder and G.J. Foschini's BLAST scheme (see Bell Labs Tech. J., p.41-59, 1996). The corresponding signal-to-noise ratio (SNR) gains can be several decibels.